Diversification, selective sweep, and body size in the invasive Palearctic alfalfa weevil infected with Wolbachia - Tuda, Midori (Sci Rep, 2021)
The alfalfa weevil Hypera postica, native to the Western Palearctic, is an invasive legume pest with two divergent mitochondrial clades in its invading regions, the Western clade and the Eastern/Egyptian clade. However, knowledge regarding the native populations is limited. The Western clade is infected with the endosymbiotic bacteria Wolbachia that cause cytoplasmic incompatibility in host weevils. Our aim was to elucidate the spatial genetic structure of this insect and the effect of Wolbachia on its population diversity. We analyzed two mitochondrial and two nuclear genes of the weevil from its native ranges. The Western clade was distributed in western/central Europe, whereas the Eastern/Egyptian clade was distributed from the Mediterranean basin to central Asia. Intermediate mitotypes were found from the Balkans to central Asia. Most Western clade individuals in western Europe were infected with an identical Wolbachia strain. Mitochondrial genetic diversity of the infected individuals was minimal. The infected clades demonstrated a higher nonsynonymous/synonymous substitution rate ratio than the uninfected clades, suggesting a higher fixation of nonsynonymous mutations due to a selective sweep by Wolbachia. Trans-Mediterranean and within-European dispersal routes were supported. We suggest that the ancestral populations diversified by geographic isolation due to glaciations and that the diversity was reduced in the west by a recent Wolbachia-driven sweep(s). The intermediate clade exhibited a body size and host plant that differed from the other clades. Pros and cons of the possible use of infected-clade males to control uninfected populations are discussed.